Control de emisiones para jeep wagoneer 1979 con convertidor catalítico - Carrera Fernandez, Julio Cesar (2014)
Since the born of internal combustion engines of Otto Cycle and Diesel Cycle to give a solution for mobility and obtain energy sources, it has been searched the way to control emissions of pollution gases coming from fossil fuels. Throughout the years with the tech advances it has been achieved the reduction of pollution bringing new technologies to last generation vehicles, but inside the country there is a lot of old vehicles with absences of new technologies that allow to keep high standards of pollution, causing harm to human health, breath diseases, and destroying the environment and increasing greenhouse gases. To avoid this pollution we will install a catalytic converter in an old vehicle without new tech that work with a carburetor fuel system, achieving the reduction of pollution.